MOTIVASI KERJA GURU SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI SE-KOTA PADANG - Azizah Pratiwi; Anisah Anisah; Nelfia Adi; Yulianto Santoso (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Teacher work motivation is an important factor in supporting the implementation of professional duties and improving the quality of learning in schools. However, several conditions are still found that indicate that teacher work motivation is not fully optimal, especially in the aspects of perseverance, self-development, and the drive to continuously improve the quality of work. This study aims to describe the work motivation of teachers in State Vocational High Schools (SMK) in Padang City based on indicators of responsibility, perseverance, self-development, and a high level of aspirations (the desire to achieve). The study used a quantitative approach with descriptive methods. The study population was 987 teachers, while a sample of 207 teachers was determined using a multistage stratified random sampling technique consisting of cluster sampling and proportional random sampling. Data were collected through a Likert scale questionnaire that had met validity and reliability tests, then analyzed using descriptive statistics with an average value (mean). The results showed that teacher work motivation was in the high category with an overall average score of 4.38. The responsibility indicator obtained an average score of 4.40, perseverance 4.36, self-development 4.38, and a high level of aspirations 4.41. These findings indicate that teachers exhibit professional commitment, responsibility, a passion for developing competencies, and a strong desire to achieve. However, the aspect of perseverance still requires greater attention to ensure teachers are more consistent in facing challenges and completing tasks optimally. The implications of this research are expected to serve as a consideration for schools and policymakers in designing programs to continuously improve teacher work motivation, particularly through professional development, strengthening work culture, and providing support that encourages optimal performance.